2018
DOI: 10.14440/bladder.2018.582
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive voiding assessment in conscious mice

Abstract: OBJECTIVE: To review available options of assessing murine bladder function and to evaluate a non-invasive technique suitable for long-term recording. METHODS: We reviewed previously described methods to record rodent bladder function. We used modified metabolic cages to capture novel recording tracings of mouse micturition. We evaluated our method in a pilot study with female mice undergoing partial bladder outlet obstruction or sham operation, respectively; half of the partial obstruction and sham group rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…11,33 However, inhibition of S6K as opposed to the entire mTOR pathway in mice during obstruction lead to worsening of bladder hypertrophy. 7 Herein, it was observed that BDNF induces extracellular signal-regulated kinase and S6K1 and is associated with loss of differentiation in BSMCs, consistent with previous studies. 10 In particular, high-dose sustained BDNF signaling may play a role in bladders by causing sustained extracellular signal-regulated kinase signaling, which is known to have differential effects on BSMC growth and neurons.…”
Section: Bdnf Signals To Proproliferative Pathways In Bladder Smooth supporting
confidence: 91%
“…11,33 However, inhibition of S6K as opposed to the entire mTOR pathway in mice during obstruction lead to worsening of bladder hypertrophy. 7 Herein, it was observed that BDNF induces extracellular signal-regulated kinase and S6K1 and is associated with loss of differentiation in BSMCs, consistent with previous studies. 10 In particular, high-dose sustained BDNF signaling may play a role in bladders by causing sustained extracellular signal-regulated kinase signaling, which is known to have differential effects on BSMC growth and neurons.…”
Section: Bdnf Signals To Proproliferative Pathways In Bladder Smooth supporting
confidence: 91%
“…Although cell biology and molecular biology have developed rapidly [ 16 , 17 ], the use of animal models to observe the biological activities and overall status of the body is necessary [ 18 ]. Rodent models are important for studying bladder physiology and pathophysiology [ 19 ]. Currently, the most commonly used surgical procedure for establishing an overactive bladder model is the creation of a partial bladder outlet obstruction [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is high variability and high mortality in traditional obstruction as the bladder neck and ureters are minute and susceptible to damage during surgery. By measuring bladder function non-invasively in NeMO (15,16,28), we could determine the efficacy of treatments without a high baseline mortality rate or secondary effects of sham surgeries.…”
Section: Discussionmentioning
confidence: 99%